“Fire and Flame”: Anna Dengel and the Medical Mission to Women and Children - Dries, Angelyn (Missiology, 1999)
In 1942, Anna Dengel (1892–1980) noted that “history has been defined as a series of biographies.” This aptly applies to the development of the Society of Catholic Medical Missionaries, the first Roman Catholic congregation of women religious which she founded for the exclusive purpose of providing professional medical assistance as surgeons, midwives, and obstetricians for those most in need. After four years as a lay mission doctor in Rawalpindi, India, Austrian-born Dengel founded the Society in 1925 in Washington, D.C. Almost seven hundred women from five continents are members of the Society today. Dengel's biography illustrates intrepid, creative medical mission leadership especially to assist women and children, in spite of ecclesiastical and cultural hindrances. Her life demonstrates a mission approach that intricately weaves science and religion, social analysis and spirituality.